The correlation between OSA-related quality of life and two mental statuses in adolescent Chinese patients with cleft palate: A comprehensive study - Zong, Yuan; Cheng, Xu; Xia, Weiyao; Xie, Zhuojun; Yang, Yichun; Shi, Bing; Gong, Caixia; Huang, Hanyao (Frontiers in Pediatrics, 2022)
Objectives: To analyze obstructive sleep apnea (OSA)-related quality of life (QoL), the statuses of depression and anxiety, and to reveal the correlation between OSA-related QoL and two mental statuses in Chinese adolescent patients with cleft palate (CP). Methods: The Obstructive Sleep Apnea Questionaire-18 (OSA-18), the Generalized Anxiety Disorder Scale (GAD-7) and the Patient Health Questionnaire-9 (PHQ-9) were applied to assess OSA-related QoL and the statuses of anxiety and depression in Chinese adolescent patients with CP, respectively. Non-CP adolescents were also included in the control group. OSA-related QoL and the two mental statuses were compared between the study and control groups. The correlation between the OSA-related QoL and two mental statuses was estimated in Chinese adolescent patients with CP. Results: A total of 8.7% patients showed a moderate or high impact of OSA on QoL, while all the adolescents from the control group showed little impact. The mean total OSA-18 score of the study group (36.261±13.500) was significantly higher than the control (28.435±8.934). The mean PHQ-9 scores of the study group and the control group were statistically different (3.957 vs. 2.113). The GAD-7 score in the study group was slightly higher than the control group (3.043 vs. 2.194), while the proportion of moderate-severe anxiety in the study group was relatively larger than that in the control group (6.5% vs. 1.6%). Moreover, there was a positive correlation between the OSA-related QoL and the statuses of anxiety and depression respectively, and the differences in GAD-7 and PHQ-9 scores between the moderate or high impact group and the little impact group were statistically significant. Conclusion: Chinese adolescents with CP reported a rate of moderate or high impact of OSA on QoL of 8.7%, which was significantly higher than adolescents without CP. The OSA-related QoL was worse and depression was severer in Chinese CP adolescents than in the control, while anxiety and depression in Chinese CP adolescents were associated with OSA-related QoL.